DNA-based algorithm for coloring a map of four research questions - Zhao Song; Li Yingmei Li (2011 International Conference on Computer Science and Network Technology, 2011)
There are four color on the map algorithm is based on the DNA chip technology of genetically modified organisms, by now fairly complete fluorescent color simulation software to analyze problems, and to the solution of problems by an algorithm. This article first four-color diagram into a directed graph, and the general model of DNA Algorithm undirected graph to solve the four-color map coloring the solution to the problem, explained through an example of using DNA simulation algorithm to the specific Coloring steps to prove the feasibility of the algorithm, and will be chaos and neural network algorithms to compare four coloring.